Crystal structure of BaBi2Ta2O9 - Paiva-Santos, Carlos O. [UNESP]; Mazon, Talita [UNESP]; Zaghete, Maria A. [UNESP]; Campos, André L. [UNESP]; Varela, José Arana [UNESP]; Foschini, Cesar R. [UNESP] (Cambridge University Press (CUP), 2000)
The crystal structure of the Aurivillius compound Bi2BaTa2O9 prepared via the chemical route was determined by direct methods using EXPO97, and refined using the Rietveld method with conventional X-ray diffraction data. The structure was found to be tetragonal (space group I4/mmm, number 139) and Z = 2, isomorphic of the Bi2BaNb2O9 reported by Blake and co-workers in the literature (1997). Two refinements were performed using the two asymmetry functions of DBWS-9807 (release 20/May/99). The unit cell for each case are: a = 3.932 22(6) Å, c = 25.5053(6) Å (RA) and a = 3.93250(7) Å, c = 25.5069(6) Å (RCF). The differences for atom positions, interatomic distances and angles are in the range of one standard deviation. Final agreements factors are: Rwp = 7.97%, S = 1.84, RBragg = 4.28%(RA), Rwp = 7.98%, S = 1.84, RBragg = 4.30% (RCF). The occupancies of Ba and Bi in site 2b were refined but constrained to have their summation equal to 1.00. The same constraints were applied to the Ba and Bi of the 4e site. The results show that on site 2b there are 70% of Ba and 30% of Bi and on the site 4e there are 82% of Bi and 18% of Ba. The charge equilibrium is maintained for one standard deviation of the site occupancies. © 2000 International Centre for Diffraction Data.